Diagnosis and therapy of adult type-2 inflammation chronic rhinosinusitis: a systematic literature review - Budi Santoso; Dinar Rosmala (Universitas 'Aisyiyah Yogyakarta, 2026)
Adult type-2 inflammation chronic rhinosinusitis with nasal polyp impacts quality of life. Despite diagnosis and treatment advances, recurrence is common, prompting the exploration of new diagnosis and therapies. Objectives To review the current literature for the best diagnosis and therapy of adult type-2 inflammation chronic rhinosinusitis and future research to find new specific diagnoses and therapies. We conducted a literature review of PubMed, Google Scholar, Cochrane Library and others, August, 2 - 9, 2025. The search terms included “type-2 inflammation”, “chronic rhinosinusitis”, and “therapy”. We got 107 e-journals from: PubMed: 13, Google scholar: 11, Cochrane Library: 14, Others: 69. Type 2 inflammation is responsible for driving the disease in 80% to 90% of patients with nasal polyps (CRSwNP) and biomarkers for diagnosis include tissue/blood eosinophils, total IgE, and interleukin. Type 2 inflamation CRSwNP have high recurrence rates 38% to 60% at 12 months follow-up, and resistance to conventional medical or surgical treatment. Effectiveness of recent treatment for severe type 2 CRSwNP: corticosteroid effective for rapid reduction of inflammation, Endoscopic Sinus Surgery (ESS) is effective for restoring sinus drainage, and biological agents promosing future treatment. Future studies should investigate the optimal diagnostic techniques for individual patients based on underlying pathophysiology especially endotype and biomarker to better direct treatment and should assess the role of new therapies. The treatment of corticosteroid combine with antihistamine, new biologics agent and new surgery technic promising strategy for achieving therapeutic benefits type-2 inflammation chronic rhinosinusitis.